Lab-Scale production of Bacillus atrophaeus' spores by solid state fermentation in fifferent types of bioreactors - Sella,Sandra Regina Barroso Ruiz (2009)
Studies were conducted to evaluate Bacillus atrophaeus spores' production by solid-state fermentation (SSF) using sugarcane bagasse as support and soybean molasses as substrate at lab-scale in column bioreactors (forced aeration), plastic bags and Erlenmeyer flasks (aeration by diffusion). Different moisture contents (84%, 86% and 88%; 89%, 91% and 93%) and aeration rates (30mL/min, 45mL/min, 60mL/min and 90mL/min) were studied. The best condition for spore production (3.3x10(10) CFU.g-¹dry matter) in column bioreactor was 80% of initial humidity and no aeration. In Erlenmeyer flasks and plastic bags the best sporulation production reached 1.7 up to 4.7x10(10) CFU.g-1dry matter with 88-93% of initial moisture. The aeration rate had no significant effect on the spore yield. The initial moisture had a significant effect depending on the bioreactor type. Sporulation kinetic's assay was carried out and it showed the possibility to reduce the time of spore formation in two days.